2015
DOI: 10.1021/acs.jpca.5b05178
|View full text |Cite
|
Sign up to set email alerts
|

Quantum State-to-State Dynamics of the H + LiH → H2 + Li Reaction

Abstract: State-to-state quantum dynamics calculations for the H + LiH (v = 0-1, j = 0) → H2 + Li reactions are performed based on an ab initio ground electronic state potential energy surface (PES). Total and product state-resolved integral and differential cross sections and rate constants are calculated. The present total integral cross sections and rate constants for the H + LiH (v = 0, j = 0) reaction are found to be in agreement with previous literature results. Product state-resolved integral cross sections and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 63 publications
4
29
1
Order By: Relevance
“…Such differences may arise due to the difference between the exoergicity of the two reactions as the neutral reaction is less exoergic (Δ E ≈ −2.258 eV) than the present ionic reaction. For lower v ′ levels, products are rotationally excited, and for higher v ′ levels, products are rotationally cold akin to the j ′ distributions for the neutral counterpart of the reaction R1 . Similar observations are also reported under cold and ultracold conditions by Roy and Mahapatra .…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Such differences may arise due to the difference between the exoergicity of the two reactions as the neutral reaction is less exoergic (Δ E ≈ −2.258 eV) than the present ionic reaction. For lower v ′ levels, products are rotationally excited, and for higher v ′ levels, products are rotationally cold akin to the j ′ distributions for the neutral counterpart of the reaction R1 . Similar observations are also reported under cold and ultracold conditions by Roy and Mahapatra .…”
Section: Resultssupporting
confidence: 79%
“…Similar observations can be made for LiH + ( v = 1, j = 0) and LiH + ( v = 0, j = 1), for which the product rotational level resolved state-to-state ICSs are shown in Figures S4 and S5. The above observation is in contrast to the neutral H + LiH → H 2 + Li reaction where a broad range of j ′ distribution has been found . Such differences may arise due to the difference between the exoergicity of the two reactions as the neutral reaction is less exoergic (Δ E ≈ −2.258 eV) than the present ionic reaction.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…Under these circumstances, the relative importance of the largest values of J gets smaller. Results presented in Figure are in good accordance with the mechanistic analysis of the H + LiH reaction performed by He et al for rotationless reactants; in the range of collision energies studied, up to 0.6 eV, the authors found the collisions to be dominated by a stripping mechanism giving rise to forward scattering and corresponding to medium and large values of J .…”
Section: General Features Of the H + Lih → LI + H2 Collisionssupporting
confidence: 92%
“…Compared to scalar observables, and exceptions notwithstanding, ,,, the mechanism of reaction and the vectorial observables more directly connected to it have received little attention. However, it is possible to extract an overall picture of the mechanism behind the H + LiH reactive collisions from the studies already available in the literature.…”
Section: Introductionmentioning
confidence: 99%